PENGEMBANGAN AIR TERJUN DLUNDUNG UNTUK MENJADI DESTINASI PARIWISATA UNGGULAN DI KABUPATEN MOJOKERTO - HANDOKO, RUDI TRI (Jurnal Manajemen Pelayanan Hotel, 2018)
This aims of the study are finding the development strategy in the tourist area of the Dlundung waterfall to be excellent destination in Mojokerto. This is a descriptive qualitative research. Data collection techniques are observation, interviews, questionnaires, and documentation. Data will be analyzed by SWOT method. Strategies have been found is the increased promotion of the natural beauty of waterfalls and campgrounds, additional facilities of outbound and painball, repair and improvement of facilities, road improvements, additional services and hours of operation of public transport, improving the quality of human resources of tourism, Perhutani reports the condition of the campground to Disparta about prioritized apparatus intensively, Perhutani and Disparta give an opportunity for investors to benefit location of the campsite, ask for the role of local communities in improving the security of tourism, Perhutani maintains the cleanliness and comfort of the facilities at tourist sites, increasing community empowerment in troubleshooting facilities and accessibility. Keywords: the development strategy, excellent destination